2019
DOI: 10.1080/07434618.2018.1556730
|View full text |Cite
|
Sign up to set email alerts
|

New and emerging access technologies for adults with complex communication needs and severe motor impairments: State of the science

Abstract: Individuals with complex communication needs often use alternative access technologies to control their augmentative and alternative communication (AAC) devices, their computers, and mobile technologies. While a range of access devices is available, many challenges continue to exist, particularly for those with severe motor-control limitations. For some, access options may not be readily available or access itself may be inaccurate and frustrating. For others, access may be available but only under optimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 63 publications
0
26
0
1
Order By: Relevance
“…In the case of ALS, loss of speech is often considered the worst aspect of disease progression, necessitating augmentative communication within 1-2 years of symptom onset (Makkonen et al, 2018) . Noninvasive assistive technologies such as sip-and-puff interfaces and eye tracking have helped re-establish communication, but suffer from low information transfer rates and limited expressivity (Fager et al, 2019;Tai et al, 2008) . In contrast, speech is amongst the most intuitive and fastest means of communication, with conversational speech conveying roughly 150 words per minute (Chang and Anumanchipalli, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ALS, loss of speech is often considered the worst aspect of disease progression, necessitating augmentative communication within 1-2 years of symptom onset (Makkonen et al, 2018) . Noninvasive assistive technologies such as sip-and-puff interfaces and eye tracking have helped re-establish communication, but suffer from low information transfer rates and limited expressivity (Fager et al, 2019;Tai et al, 2008) . In contrast, speech is amongst the most intuitive and fastest means of communication, with conversational speech conveying roughly 150 words per minute (Chang and Anumanchipalli, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…A review of current levels of BCI performance was also provided to help demonstrate recent advances in the field of BCI. However, while future work must continue to focus on the development of new decoding algorithms to increase BCI performances above those outlined in this tutorial, along with identifying how to decrease the high levels of workload associated with BCI use (e.g., Koch Fager, Fried-Oken, Jakobs, & Beukelman, 2019), it is important for researchers to remain aware of how BCI will ultimately be implemented in the clinical setting , along with procedures providing at-home and caregiver support (e.g., Wolpaw et al, 2018). Thus, to help account for possible BCI performance variations and highlight how BCI is not a "one size fits all method," cognitive-sensory-motor and medical (e.g., history of seizures) factors influencing BCI outcomes were also described.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-computer interfacing has also demonstrated profound benefits in correcting blindness through phosphine generation, thereby introducing a limited field of vision to previously sightless patients [54]. Studies have shown that those patients with access to BCI technologies, get faster recoveries from serious mental and physical traumas compared to those who undergo traditional rehabilitation methods [55]. For this very reason, the use of BCI has also expanded (albeit tentatively) into the fields of Parkinson's disease, Alzheimer's disease, and dementia research [56,57].…”
Section: Bci Systems Classificationmentioning
confidence: 99%